Faecalibacterium prausnitzii enhances intestinal IgA response by host-microbe derived inecalcitol in colitis - Wenfei Qin; Nuoming Yin; Binqiang Xu; Qixiang Mei; Yang Fu; Junjie Fan; Yingying Lu; Guangqiang Wang; Lianzhong Ai; Zhanjun Lu; Yue Zeng; Chunlan Huang (BMC Medicine)
Abstract Background Faecalibacterium prausnitzii plays a crucial role in ulcerative colitis (UC) remission, but its action mechanism is unknown. Here, we aimed to explore the potential mechanisms focusing on the interaction of F. prausnitzii with host immune response and its potential modulation on gut microbiome. Methods RNA-seq analysis together with 16S rRNA sequencing and metabolomics were performed in a dextran sodium sulfate (DSS)-induced colitis mouse model followed by F. prausnitzii gavage. To present evidence of sIgA involved in the anti-inflammatory effects of F. prausnitzii, we further applied immunoglobulin A (IgA) knockout mice and secretory IgA (sIgA) depletion mouse models using polymeric immunoglobulin receptor (pIgR) neutralizing antibody. Colonic immune cells were characterized by flow cytometry. The fecal relative abundance of F. prausnitzii, inecalcitol, and colonic IgA expression were assessed in UC patients. Results F. prausnitzii markedly ameliorated colitis by alleviating intestinal inflammation and barrier dysfunction, with significantly decreased abundance of pro-inflammatory taxa (Enterococcus, Desulfovibrio, Escherichia-Shigella, and Enterorhabdus) and increased abundance of Lachnospiraceae NK4A136_group. Functions related to intestinal immune network for IgA production pathway were up-regulated shown by transcriptomics and KEGG pathway analysis. Increased expression of IgA production associated genes including MHCII-related genes, Aicda, and Tnfrsfl3c were verified, accompanied by up-regulated colonic IgA and pIgR. The IgA knockout mice and sIgA depletion model weakened the anti-inflammation and microbiota-modulation effects of F. prausnitzii, which was further proved by fecal microbiota transplantation (FMT). The shift profile of fecal metabolites after F. prausnitzii supplement was characterized by increased production of inecalcitol, which may account for the enhanced IgA response. In a cohort of UC patients, the relative abundance of F. prausnitzii was decreased and positively correlated with colonic IgA expression and negatively correlated with disease severity. Conclusions F. prausnitzii effectively alleviated colonic inflammation and modulated dysbiosis via enhancing colonic IgA response, thus showing promise as a UC treatment. Graphical Abstract